(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The Fontana Marella cave, located in the Pre-Alps in Varese province (Lombardy, North Italy), supplied a Middle Pleistocene small mammal fauna, unique for this region. Thanks to the presence of Arvicola cf. mosbachensis and Pliomys episcopalis it is possible to date this sequence to the Early Toringian. Mostly for the predominant, presence of dominant Glis glis, Chionomys nivalis and Dinaromys bogdanovi, the faunal association is attributed to a temperate period, but cooler and perhaps more arid that the present one. The find of Macroneomys is important because it allows to extend the geographic distribution of this rare species.